Facilitating secondary school teachers records keeping capacity through ICT resources utilisation in Ogun State, Nigeria (2020)
The problem of records management and retrieval has become a challenge in Nigerian schools which might not be unconnected with methods used. Traditional methods have proved to be problematic with important documents as certificates, testimonials and others usually missing. In these digital times, important documents are often either misplaced or cannot be traced giving educational administrators and stakeholders tough decision making processes. The study adopted the survey research design with a population of1,845 teachers and a sample of 218 teachers selected through simple random sampling technique. The instrument for the study is ICT resources utilization and records keeping questionnaire (ICTURKQ) developed by the researcher, face and content validated by experts in the Faculty of Education of the University of Ibadan. ICTURKQ reliability coefficient is r=0.84 using the Cronbach alpha statistic. ICTURKQ is 25 item questionnaire whose findings were analysed with frequency count percentages, independent t-tests and multiple regression analysis. Findings revealed that the level of ICT utilization for record keeping in schools in the Shagamu LGA is low. A significant difference existed in the method of records keeping between private and public secondary schools in the LGA (t=0.002;p<0.05]. Finally, ICT resources allocation and utilization was found to have a significant joint influence on records keeping with(R=0.579, R2=0.335, Adjusted R =0.332 and r=0.000;p<0.05). It was recommended that government should take more concrete steps in funding public schools to make ICT facilities and teacher training in ICT more effective and efficient to facilitate records keeping in Ogun state schools.